Development of Strategies Through a Balanced Scorecard for the Management of Human Talent and Administrative Performance in the Hotel Companies of the Province of Santa Elena - Garzozi-Pincay, René Faruk (2021)
This work is focused on showing the processes used in hotel companies for a correct administrative management carried out by the human talent that works within the company. It is worth mentioning that at present the companies define their collaborators as their main base. Its importance lies in the commitment to achieve the objectives established in the medium and long term, and to generate a high impact in the processes providing a quality service within a highly competitive market; Reason why they motivate the company to adapt to the changes to manage new systems that help to potentiate the capacities of the human talent, thus creating a competitive advantage. The main objective is to develop strategies through the implementation of the Balanced Scorecard, which allows to maintain a strategic vision of each process in the hotel companies. This study has a quantitative and qualitative approach. The methods used were inductive and deductive; In order to analyze the causes and effects that affected the problem. The type of research design is based on an exploratory, descriptive and bibliographic study that generates relevant data to develop research work. It proposes an application of integral scorecards in the hotel companies by means of which they allow to establish strategies suitable for the decision making. This tool offers us to have a different perspective from the financial field, customers, internal processes, innovation and learning perspective.